Implementasi Kurikulum Merdeka dalam Meningkatkan Mutu Pembelajaran IPS - Ramadhani, Fara Dila; Adisel, Adisel; Salamah, Salamah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to discover the independent social studies curriculum at SMP 01 South Bengkulu. The autonomous curriculum and how this curriculum helps them improve their learning is the main reason for carrying out this research. The research method used is qualitative and descriptive. The research results showed that an independent curriculum would suit the social studies program at SMP Negeri 1 South Bengkulu. Looking at the course description and creating some learning plans are two of the many steps involved in preparation. There is a big gap between teachers' teaching methods and their planned learning. The instructor does need to implement the learning plan. Student interviews and research findings indicate a need for proper implementation of core social studies activities, which causes the teaching and learning process inefficient and ineffective. This is because several sub-indicators are not included. There is nothing wrong with the closing procedure. This is because each unit ends with thought-provoking homework, an opportunity for class discussion, and a brief overview of the unit provided by the instructor. In conclusion, curriculum autonomy at SMP Negeri 1 South Bengkulu depends on the teacher's ability to inspire students to reach their maximum potential and shape their thoughts and actions to encourage sustainable progress. Keywords: Implementation of the Independent Curriculum, Social Sciences, Quality of Learning